A data-driven financial justification for an outpatient infectious diseases pharmacist - Justin J. Kim; Laura N. Hernandez Guarin; Jonathan Contreras; Mary K. Hayden; Sarah Y. Won (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
We present a financial justification for an outpatient infectious diseases pharmacist, based on cost savings from decreases in length of stay for patients with Staphylococcus aureus infections and additional revenue generated by physicians and pharmacists while following patients discharged on outpatient parenteral antimicrobial therapy.